NUTRİONAL KNOWLEDGE LEVELS OF ADULT PRİSONERS İN AMASYA, TURKEY - Örs, Mukaddes; Kalkan, Indrani (Advances in Social Sciences Research Journal, 2017)
Prisoners and convicts are deprived of important aspects of health promotion, health education and disease prevention and tend to have poorer health status in comparison to the general public. This study, was planned to determine the level of nutritional knowledge of adult prisoners and convicts in Amasya E Type Closed Penal Institution and understand the training requirement for theses individuals. The questionnaire comprising of questions aimed to measure nutriton knowledge levels were administered on 200 individualsbetween April 2014 and March 2015 by means of face-to-face interview method. Regarding training undertaken in the prison, 76.5% stated that they had not undertaken any kind of training during their stay. Of the training provided, 85.4%were in non-health related fields. Half of the participants mentioned that they obtained nutrition related knowledge from mass media as newspaper, TV and internet. Questions regarding food sources of certain nutrients were answered correctly by less than 50% of the participants. The nutrition knowledge level were found to be incorrect or limited. It was suggested that nutriton and health related trainings were to be organized at regular intervals to increase the awareness and improve food habits of the individuals.